How plain is legal English in statues? - Borisova, Lidia (Linguistica (Ljubljana), 2013)
This article analyzes whether Plain English Campaign has influenced the language of British statutes. The author enumerates some requirements plain English in legislation should satisfy and compares to what extent, if any, the drafters of legislative texts have managed to satisfy these requirements. Special attention is paid to the mostcriticized features of statutes such as archaic words and the modal shall. Some other aspects analyzed in the article are the use of Voice, Tenses, syntax and organization of British statutes. The author provides examples illustrating the points stated, outlines a perspective for further research and comments on some difficulties Plain English Campaign may face in the UK as far as the legislative texts are concerned.
Keywords: anglais; angleščina; English; Grande Bretagne; langage juridique; Plain English campaign; pravni jezik; statuti; statuts; Velika Britanija